(untitled) (Collection of scientific works «Modern structures of metal and wood», 2019)
The changes in air temperature cause additional movement in open statically determinate structures, as well as in elements of closed statically indefinable structures that don’t have a complete freedom of movement. Mathematical calculations of steel elements on the temperature displacements show that displacements which occur in free rods due to the action of temperature cause noticeable changes in the geometric scheme of construction. And in the pinched rods, stresses arise, the value of which reaches one third of the steel resistance. That is, the temperature changes in both cases significantly affect on the stress-strain state of steel rods. The frame locking period (winter or summer) in a complete statically indefinable system can also affect the internal forces in structures and on the total stress-strain state of the building. However, there is no study of the effect of this phenomenon on steel frames of real buildings in the literature. Therefore, the aim of this work is study the effect of locking period on the internal forces in the load-bearing structures of one-story buildings steel frames. A numerical experiment in which steel frames of one-span one-story buildings with dimensions of 24×108 m are simulated and calculated, in which the columns with the foundations are articulated and rigidly connected is presented. Frames were modeled in the software package Autodesk Robot Structural Analysis with the determination of internal forces and stresses in individual structures from the action of constant and variable loads, including temperature differences. Based on the results of calculations for individual loads, three design combinations of efforts were compiled: constant and variable loads without taking into account the influence of temperature; constant and variable loads, taking into account the temperature effects during summer frame locking period; constant and variable loads, taking into account the temperature effects during winter frame locking period. For further analysis, the following control parameters were selected: the greatest values of bending moments in the plane of the frame, from the plane of the frame and the greatest stresses in the group of structures. An analysis of the results showed that both with articulated and rigid fastening in the foundations, the cross section of the column is determined by the bending moment in the cornice of the frame. The cross-section of the beam is determined by the reference bending moment in the cornice of the frame. The moment in the middle of the span of the beam is approximately 1,5 times less than the reference moment when the columns are hinged and almost 2 times less with a rigid support of the columns. The maximum stresses from the influence of air temperature in the frame with the hinged support of the columns don’t exceed 1,3% of the stresses caused by the total effect of all loads, regardless of the locking period. This indicates an insignificant effect of temperature differences with small sizes of the frame in plan and the hinged type of support of the columns on the foundations. When the columns are rigidly supported on the foundations, the air temperature affects stresses to a greater extent, increasing them to 5% during summer locking period and up to 17% during winter locking period. Therefore, the choice of the period of locking period of the steel frame, taking into account the design scheme, can serve as a means of controlling the stress-strain state of the supporting structures of the frame.